Contraceptive counseling: An unaddressed issue of Post Renal transplant women of reproductive age - Khawar Sultan, Zainab Maqsood, M. Sajid Rafiq Abbasi, Shoukat Hussain, M. Arshad Abbasi, Muhammad Hussain Baloch (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Counseling regarding conceiving and contraception in post renal transplant female recipients is neglected and important aspect of post-transplant care. Aim: To conduct to report use of contraceptive measures, pregnancy and its outcomes during post-transplant period. This study highlights the importance of contraceptive counseling after renal transplant. Results: Out of total 14 patients of our study only 5 (36%) were using contraception while 9 (64%) were not using any contraceptive method. Out of 9 non users 7 patients were never counseled regarding contraception. Moreover they had no awareness regarding drug modification or renal and feto-maternal outcomes of pregnancy after renal transplant. Conclusion: Reproductive age female patients undergoing renal transplant should be given special attention regarding counselling on contraception, pregnancy and it outcomes. Key words: Contraception, renal transplant, pregnancy,